The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1093/europace/euq164
|View full text |Cite
|
Sign up to set email alerts
|

Influence of beta-blocker therapy on antitachycardia pacing effectiveness for monomorphic ventricular tachycardias occurring in implantable cardioverter-defibrillator patients: a dose-dependent effect

Abstract: Beta-blockers increase the effectiveness of ATP through a dose-dependent effect. As a result, they reduce the incidence of shocks due to VT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 26 publications
5
15
2
Order By: Relevance
“…3,20,23 In the present study, the rate of VT-related symptoms was similar to others reported previously. 3,24 However, episodes with lower degrees of R-R fluctuations and/or progressive acceleration had a higher incidence of syncope or near syncope because they were associated with a lower ATP effectiveness.…”
Section: Discussionsupporting
confidence: 92%
“…3,20,23 In the present study, the rate of VT-related symptoms was similar to others reported previously. 3,24 However, episodes with lower degrees of R-R fluctuations and/or progressive acceleration had a higher incidence of syncope or near syncope because they were associated with a lower ATP effectiveness.…”
Section: Discussionsupporting
confidence: 92%
“…In our study population, VT cycle length, ATP pacing rate, cycle length variability, and EGM‐morphology did not predict ATP efficacy. In agreement with previous reports, beta‐blockers improved the success rate of ATP. Indeed, beta‐blockers prolong the excitable gap, thereby facilitating ATP to enter in the VT circuit …”
Section: Discussionsupporting
confidence: 92%
“…19 Blockade of beta-adrenergic receptors has consequently been shown to increase ATP efficacy. 20 Pacing stimulus for ATP delivery is conventionally expressed as a percentage of the tachycardia cycle length for a given R-R interval from 0 to 100 from the onset of the preceding R wave. Pace stimulation delivered at shorter coupling intervals (ie, o85%) may be more likely to enter the circuit but also accelerate the arrhythmia 21 unless delivered in a shortened train of 5 pulses.…”
Section: Atp: Rationale For Use and Supportive Clinical Evidencementioning
confidence: 99%